Prevalence and factors associated with suboptimal adherence to dolutegravir-based regimens among people living with HIV in a specialized clinic in Kampala, Uganda. A cross-sectional study. - Namakula, Edith; Mugerwa, Henry; Kitutu, Freddy Eric; Kawuma, Aida N; Ronald Kiguba, Ronald Kiguba; Kalyango, Joan N (Student's Journal of Health Research Africa, 2025)
Background: In Uganda, 54% of people living with HIV(PLHIV) on first-line Antiretroviral Therapy (ART) were taking dolutegravir-based regimens. This study aimed to determine the prevalence and factors associated with suboptimal adherence to dolutegravir-based regimens among PLHIV at a specialized clinic in Uganda. Methods: A cross-sectional study was conducted at a specialized HIV clinic in Kampala, Uganda, from July to August 2022. Quantitative data were collected using questionnaires and data abstraction tools from 366 consecutively sampled and consented PLHIV. Adherence was measured using a modified Morisky Medication Adherence Scale, which consisted of 9 questions. Qualitative data were collected using in-depth interviews among 13 purposively sampled, consented participants. Quantitative data were analysed using modified Poisson regression in STATA 14 to obtain factors associated with suboptimal adherence at the 5% level of significance. Qualitative data were analyzed using thematic analysis in Open Code version 4.03. Results: The median age of participants was 44 (IQR: 35 to 52), while 64.8% (237/366) were female. The prevalence of suboptimal adherence to dolutegravir-based regimens was 49% (179/366; 95%Confidence Interval (CI): 44, 54). Alcohol consumption (adjusted Prevalence Ratio (aPR): 1.25; 95%CI: 1.012, 1.543), and unemployment (aPR: 1.27; 95%CI: 1.002, 1.609) were associated with a higher likelihood of suboptimal adherence while the lack of social support (aPR: 0.78; 95%CI: 0.619, 0.993), and talking to the doctor in case of a health problem (aPR: 0.44; 95%CI: 0.307, 1.270) were protective against suboptimal adherence, to dolutegravir-based ART regimens. Barriers to dolutegravir adherence included unemployment, lack of social support, alcohol consumption, and inadequate counseling. Conclusion: Suboptimal adherence to dolutegravir-based ART was high. Alcohol consumption, unemployment, lack of social support, and inadequate counselling influenced dolutegravir adherence. Recommendations: Start-up projects to address unemployment should be implemented for PLHIV. Dolutegravir-related virological failure resulting from non-adherence in PLHIV should be investigated.